The Impact of Capital Adequacy on Islamic Banks Financial Performance -An Econometric study of "Saudi Al-Rajhi Bank" During - (2020-2010) - bourazi, widad; lafifi, derradji (Journal of Research in Finance and Accounting, 2022)
The study aims to determine the impact of capital adequacy on the financial performance in Alrajhi Islamic Bank during .(2020-2010) Both ratios, return on assets and return on equity, are adopted to measure the bank’s financial performance using the autoregressive model. Findings show an opposite relationship between capital adequacy and profitability ratios in Alrajhi Bank. Moreover, there is a one-way causal relationship between capital adequacy and return on assets (ROA). In addition, there is no causal relationship in both directions between capital adequacy and return on equity (ROE).